Discussion on the common sense of the Internet of things - Yu SUN (物联网学报)
The development of Internet of things (IoT) in China is in the second decade.First of all,the outcome of the IoT was reviewed.The industry formation and system structure of IoT were introduced.Then,the development process,trends and key points of the next generation of IoT were summarized in the aspect of the service platform,sensor industry,access links and fusion with technologies such as cloud computing,edge computing,big data,identity resolution,blockchain,satellite navigation system,5G and so on.Finally,the problems and possible ideas of the development of IoT in China were put forward in the fields of the application positioning,theoretical research,standard-setting and security.Hope to provide reference for colleagues to understand the IoT.